One-step synthesis of pure pyrite FeS2 with different morphologies in water. (3rd March 2015) - Yuan, Binxia; Luan, Weiling; Tu, Shan-tung; Wu, Jiang
Abstract : Through the adjustment of the volume ratio of ETA and H2 O, cubic, flake-like, tetrakaidecahedron, hollow sphere, and rod-like structures are observed. Abstract : In this study, pyrite FeS2 with novel nanostructures had been obtained via an ethanolamine (ETA)–water binary system. This method provided a uniform and homogenous environment for the nucleation and growth of FeS2 . When only pure water was used as the reaction solvent, marcasite FeS2 with a hollow sphere structure was achieved, and then transformed into the pyrite phase with a rod-like structure piled up by nanoparticles with the increase of the reaction time. Moreover, cubic, flake-like, and two types of tetrakaidecahedron structures were obtained via the adjustment of the volume ratio of ETA and H2 O. The transformation mechanism from flower-like amorphous to different types of morphologies of pyrite FeS2 crystals was analyzed through the time-dependent controlled experiments. The Raman spectra of the samples with different morphologies were investigated, which were consistent with the XRD analysis. The studies of optical properties indicate that the morphologies had a great influence on the absorption properties. This study provided a very simple and low cost method to control the morphologies of FeS2 crystals, which would be of great potential for the synthesis of other metal chalcogenides and lay the foundation for the development of solar cells.